The Impact of Race on the Health of South Asians: A Systematic Review - Muralitharan, Maiura (My University, 2023)
Background: Race, or specifically racism, has been well-established as a critical determinant of health, though current healthcare practices and policies in Western countries do not adequately address these issues. South Asians are the largest minority group in Canada, and they face disproportionate rates of chronic illnesses, mental health conditions, and barriers to care globally. However, their experiences in healthcare settings and the impact of race and racism on their health equity remain unexplored. This systematic review examined whether race affects healthcare access, utilization, and outcomes of South Asians compared to White-majority populations in Western countries. Methods: Embase, PsycInfo, Ageline, and CINAHL, were searched following PRISMA guidelines, as well as Google Scholar. Articles from 2013-2022 were included if they discussed racism, discrimination, or disparities/inequalities in South Asian physical and mental health, healthcare access, and utilization, outcomes compared to White populations in Canada, the U.K., the U.S.A., Australia, and New Zealand. The Mixed Methods Appraisal Tool (MMAT) was used to assess methodological quality. Data was synthesized narratively. Results: The review included 89 studies from Canada (n=19), the U.K. (n=51), the U.S.A. (n=17), and Australia (n=2), with most studies (n=76) utilizing cross-sectional or cohort designs and examining physical health outcomes (n=50). Study samples predominantly included Indians, Pakistanis, and Bangladeshis over other subgroups. Notably, there was no overall increase in comparative studies over the last decade; however, the U.K. observed an 85% increase compared to an 82% and 64% decrease in Canada and the U.S.A., respectively. The review also identified limited research on experiences within healthcare settings and mental health outcomes, sexual/reproductive health, and all health outcomes for children/youth. Few studies directly discussed the impacts of structural or organizational racism or discrimination on outcomes, though some commented on individual racism as well. Instead, studies relied on the social determinants of health as proxies for structural racism, such as education and income. Conclusion: This review highlights the significant lack of comparative research on the impact of structural, organizational, and individual racism on the healthcare access, utilization, and outcomes of South Asians compared to White-majority populations in Western countries. The review emphasizes the need for more primary, comparative research that quantifies and contextualizes South Asian experiences in obtaining healthcare services. Future research must employ rigorous and representative sampling methods, diverse study designs, and quantitative and qualitative measures that capture implicit, covert, and overt racism in healthcare among South Asians. Additionally, studies should measure factors such as religion, housing, language, and racialized institutional policies, in addition to the typically examined social determinants of health. Finally, this review highlights the need to collect and report disaggregated race and ethnicity health data with input from community leaders, and stratify these data by South Asian subgroups to avoid homogenization of distinct cultures and differential experiences in healthcare systems. Overall, acknowledging racism in healthcare and institutional policies is essential to effectively dismantle these issues and ensure health equity for South Asians.
This systematic review examined literature spanning the last 10 years from Canada, the U.K., the U.S.A., Australia, and New Zealand. Findings highlight the significant gap in comparative literature examining (structural) racism as a determinant of South Asian healthcare access, utilization, and outcomes, and identifies areas of future research to address South Asian health equity concerns.
Keywords: Racism; Race; South Asian; Health disparity; Health inequity; Critical Race Theory; Structural racism; Social Determinants of Health